Docetaxel plus cisplatin and S-1 versus cisplatin and S-1 in patients with advanced gastric cancer (JCOG1013): an open-label, phase 3, randomised controlled trial. (July 2019) - Yamada, Yasuhide; Boku, Narikazu; Mizusawa, Junki; Iwasa, Satoru; Kadowaki, Shigenori; Nakayama, Norisuke; Azuma, Mizutomo; Sakamoto, Takeshi; Shitara, Kohei; Tamura, Takao; Chin, Keisho; Hata, Hiroaki; et al.
Summary: Background: We investigated the superiority of docetaxel plus cisplatin and S-1 compared with cisplatin and S-1 in chemotherapy-naive patients with advanced gastric cancer. Methods: In this open-label, phase 3, randomised controlled trial, patients were recruited from 56 hospitals in Japan. We enrolled individuals aged 20–75 years who had unresectable or recurrent gastric cancer, had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1, had received no previous chemotherapy (except adjuvant chemotherapy completed 24 weeks before reccurence), radiotherapy, or hormonal therapy, could take drugs orally, and had adequate organ function. Patients were randomly assigned (1:1) to receive docetaxel plus cisplatin and S-1 (docetaxel 40 mg/m 2 and cisplatin 60 mg/m 2 on day 1 intravenously, and S-1 40–60 mg twice a day orally for 2 weeks, every 4 weeks) or cisplatin and S-1 (cisplatin 60 mg/m 2 intravenously on day 8, and S-1 40–60 mg orally twice a day for 3 weeks, every 5 weeks). Randomisation was done centrally with the minimisation method, with a random component balancing for institution, ECOG performance status (0 vs 1), disease status at enrolment (unresectable vs recurrent), measurable lesion (yes vs no), number of metastatic sites (0–1 vs ≥2), and histological type (differentiated vs undifferentiated). Neither investigators or patients were masked to the study treatment. The primary endpoint was overall survival in the intention-to-treat population. The study is registered with UMIN-CTR, number UMIN000007652. Findings: Between April 3, 2012, and March 18, 2016, 741 patients were randomly assigned to receive docetaxel plus cisplatin and S-1 (n=370) or cisplatin and S-1 (n=371). Median overall survival was 14·2 months (95% CI 12·9–15·9) in the docetaxel plus cisplatin and S-1 group and 15·3 months (14·2–16·2) in the cisplatin and S-1 group (hazard ratio [HR] 0·99 [95% CI 0·85–1·16]; one-sided stratified log-rank p=0·47). The most common grade 3 or worse adverse events were neutropenia (209 [59%] of 357 patients in the docetaxel plus cisplatin and S-1 group vs 117 [32%] of 365 patients in the cisplatin and S-1 group), leukopenia (120 [34%] vs 60 [16%]), and anorexia (94 [26%] vs 81 [22%]). The deaths of one patient in the cisplatin and S-1 group and in three patients in the docetaxel plus cisplatin and S-1 group were deemed treatment-related. Interpretation: The addition of docetaxel to cisplatin and S-1 did not improve overall survival in chemotherapy-naive Japanese patients with advanced gastric cancer. Therefore, cisplatin and S-1 remains the standard first-line chemotherapy. Funding: Ministry of Health, Labour and Welfare and Japan Agency for Medical Research and Development.